Barbarians Speaking – The Historiographical Theater and Its Effect in Henry of Latvia’s Chronicon Livoniae - Markevičiūtė, Ramunė (Literatūra, 2017)
Since the times of Herodotus, historiographic accounts have been written employing dramatic narration, thus granting historical figures immediate appearance through direct speech. This kind of historiographical theater, considered to be fictive and unreliable by modern historiographical critique, has a tradition and function in medieval historical accounts. The present paper analyses the purpose and the effect of dramatic narration in medieval texts, focusing on examples in Henry of Latvia’s Chronicon Livoniae. In examining the utterances in direct speech in more detail, it aims to disclose the image of the native peoples in the Baltic, the Barbarians, the way it is constructed by the author, and to determine the significance of dramatic narration in a historical account.
Keywords: Medieval historiography; drama; Henry of Latvia; Chronicon Livoniae; dramatic narration; Baltic Crusades; the Barbarians